Differential Attachment of Salmonella enterica and Enterohemorrhagic Escherichia coli to Alfalfa, Fenugreek, Lettuce, and Tomato Seeds - Cui, Yue (Appl Environ Microbiol, 2017)
Vegetable seeds have the potential to disseminate and transmit foodborne bacterial pathogens. This study was undertaken to assess the abilities of selected Salmonella and enterohemorrhagic Escherichia coli (EHEC) strains to attach to fungicide-treated versus untreated, and intact versus mechanically damaged, seeds of alfalfa, fenugreek, lettuce, and tomato. Surface-sanitized seeds (2 g) were exposed to four individual strains of Salmonella or EHEC at 20°C for 5 h. Contaminated seeds were rinsed twice, each with 10 ml of sterilized water, before being soaked overnight in 5 ml of phosphate-buffered saline at 4°C. The seeds were then vortexed vigorously for 1 min, and pathogen populations in seed rinse water and soaking buffer were determined using a standard plate count assay. In general, the Salmonella cells had higher attachment ratios than the EHEC cells. Lettuce seeds by unit weight had the highest numbers of attached Salmonella or EHEC cells, followed by tomato, alfalfa, and fenugreek seeds. In contrast, individual fenugreek seeds had more attached pathogen cells, followed by lettuce, alfalfa, and tomato seeds. Significantly more Salmonella and EHEC cells attached to mechanically damaged seeds than to intact seeds (P < 0.05). Although, on average, significantly more Salmonella and EHEC cells were recovered from untreated than fungicide-treated seeds (P < 0.05), fungicide treatment did not significantly affect the attachment of individual bacterial strains to vegetable seeds (P > 0.05), with a few exceptions. This study fills gaps in the current body of literature and helps explain bacterial interactions with vegetable seeds with differing surface characteristics. IMPORTANCE Vegetable seeds, specifically sprout seeds, have the potential to disseminate and transmit foodborne bacterial pathogens. This study investigated the interaction between two important bacterial pathogens, i.e., Salmonella and EHEC, and vegetable seeds with differing surface characteristics. This research helps understand whether seed surface structure, integrity, and fungicide treatment affect the interaction between bacterial cells and vegetable seeds.